124k views
5 votes
PLS HELP ASAP!

In the equation 6x − 2 = −4x + 2, Spencer claims that the first step is to add 4x to both sides. Jeremiah claims that the first step is to subtract 6x from both sides. Who is correct? Explain.



PLS HELP ASAP! In the equation 6x − 2 = −4x + 2, Spencer claims that the first step-example-1
User Jgp
by
5.3k points

1 Answer

4 votes

Answer:

Explanation:

either way works, but I would suggest adding 4x to each side so that the "x" value stays postive. Keeping the "x" positive when possible always helps me.

it becomes:

10x=4

x=4/10

x=2/5

User Fittoburst
by
5.2k points